2014
DOI: 10.1371/journal.pone.0102302
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Bt Rice Pollen Containing Cry1C or Cry2A Protein Poses a Low to Negligible Risk to the Silkworm Bombyx mori (Lepidoptera: Bombyxidae)

Abstract: By consuming mulberry leaves covered with pollen from nearby genetically engineered, insect-resistant rice lines producing Cry proteins derived from Bacillus thuringiensis (Bt), larvae of the domestic silkworm, Bombyx mori (Linnaeus) (Lepidoptera: Bombyxidae), could be exposed to insecticidal proteins. Laboratory experiments were conducted to assess the potential effects of Cry1C- or Cry2A-producing transgenic rice (T1C-19, T2A-1) pollen on B. mori fitness. In a short-term assay, B. mori larvae were fed mulber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…For example, recent laboratory experiments were conducted to assess the potential effects of Cry1C‐ or Cry2A‐producing transgenic rice (T1C‐19, T2A‐1) pollen on B. mori fitness. B. mori larvae were not negatively affected when fed mulberry leaves covered with pollen from Bt rice lines for 3 days, even when Bt rice pollen density was at 1800 pollen grains/cm 2 mulberry leaf, which is much higher than the mean natural density of rice pollen on leaves of mulberry trees (93 grains/cm 2 leaf) near paddy fields (Yang et al ., ). In the long‐term assay, the larvae were fed Bt and control pollen for their entire larval stage (approximately 27 days), which was significantly longer than the rice pollen shedding duration, B. mori larvae were negatively affected at Bt pollen densities exceeding 150 grains/cm 2 leaf (Yang et al ., ).…”
Section: Issues Facing Adoption Of Bt Rice In Chinamentioning
confidence: 97%
See 4 more Smart Citations
“…For example, recent laboratory experiments were conducted to assess the potential effects of Cry1C‐ or Cry2A‐producing transgenic rice (T1C‐19, T2A‐1) pollen on B. mori fitness. B. mori larvae were not negatively affected when fed mulberry leaves covered with pollen from Bt rice lines for 3 days, even when Bt rice pollen density was at 1800 pollen grains/cm 2 mulberry leaf, which is much higher than the mean natural density of rice pollen on leaves of mulberry trees (93 grains/cm 2 leaf) near paddy fields (Yang et al ., ). In the long‐term assay, the larvae were fed Bt and control pollen for their entire larval stage (approximately 27 days), which was significantly longer than the rice pollen shedding duration, B. mori larvae were negatively affected at Bt pollen densities exceeding 150 grains/cm 2 leaf (Yang et al ., ).…”
Section: Issues Facing Adoption Of Bt Rice In Chinamentioning
confidence: 97%
“…Previous studies showed significant differences in toxicity of pollen from different Bt rice lines to silkworms (Wang et al ., , ; Yang et al ., ; Yao et al ., , ; Yuan et al ., ). The differing results may be attributed to (i) different types of Bt proteins expressed in pollen; (ii) different expression levels of Bt proteins contained in pollen; and (iii) different levels at which silkworm larvae were exposed to Bt protein in the respective feeding studies (Yang et al ., ; Yao et al ., ). In addition, different silkworm varieties showed significantly different sensitivities to the same Bt protein (Yuan et al ., ).…”
Section: Issues Facing Adoption Of Bt Rice In Chinamentioning
confidence: 99%
See 3 more Smart Citations